Evaluation of Tinospora cordifolia Willd. Extracts Against Algal Growth - Al -Haidari , Alaa M. Dh.; Al –Shahwany, Ayyad W. R.; Hassan , Ghufran M. (Iraqi Journal of Science, 2022)
The present study has been conducted to evaluate the antialgal activities ofTinospora cordifolia leaves extracts, these extracts included Terpens, Alkaloids, andPhenols of that plant against 3 algal isolates: Anabaena circinalis, Scenedsmusquadricauda and Mougeotia scalaris. The agar well diffusion method was used toevaluate the inhibitory actions of these extracts with 3 concentrations: 5, 10, and 20mg/ml. The experiments were conducted and analyzed as factorial experiments withthree replications using a completely Randomized Design, Means were comparedaccording to L.S.D. values at 5% significant level.Results showed that A. circinalis was the most sensitive to alkaloid extract andthe diameterinhibitionzone was 40 mm in 20 mg/ml concentration, while this algawas less sensitive to phenol extract anthe inhibition zone was 17 mm. also theresults showed that alkaloids extract was most active against all algae usedin thisstudy followed by terpens extracts, while the phenols extracts had lower antialgalactivity.